Confirmation of Insertion, Deletion, and Deletion-Insertion Variants Detected by Next-Generation Sequencing. - Choate, Lauren A.; Koleilat, Alaa; Harris, Kimberley; Vidal-Folch, Noemi; Guenzel, Adam; Newman, Jessica; Peterson, Brenda J.; Peterson, Sandra E.; Rice, Christopher S.; Train, Laura J.; Hasadsri, Linda; Marcou, Cherisse A.; et al. (Clinical Chemistry, 2023)
BACKGROUND: Despite clinically demonstrated accuracy in next generation sequencing (NGS) data, many clinical laboratories continue to confirm variants with Sanger sequencing, which increases cost of testing and turnaround time. Several studies have assessed the accuracy of NGS in detecting single nucleotide variants; however, less has been reported about insertion, deletion, and deletion-insertion variants (indels). METHODS: We performed a retrospective analysis from 2015-2022 of indel results from a subset of NGS targeted gene panel tests offered through the Mayo Clinic Genomics Laboratories. We compared results from NGS and Sanger sequencing of indels observed in clinical runs and during the intra-assay validation of the tests. RESULTS: Results demonstrated 100% concordance between NGS and Sanger sequencing for over 490 indels (217 unique), ranging in size from 1 to 68 basepairs (bp). The majority of indels were deletions (77%) and 1 to 5 bp in length (90%). Variant frequencies ranged from 11.4% to 67.4% and 85.1% to 100% for heterozygous and homozygous variants, respectively, with a median depth of coverage of 2562×. A subset of indels (7%) were located in complex regions of the genome, and these were accurately detected by NGS. We also demonstrated 100% reproducibility of indel detection (n = 179) during intra-assay validation. CONCLUSIONS: Together this data demonstrates that reportable indel variants up to 68 bp can be accurately assessed using NGS, even when they occur in complex regions. Depending on the complexity of the region or variant, Sanger sequence confirmation of indels is usually not necessary if the variants meet appropriate coverage and allele frequency thresholds.